2023
DOI: 10.3390/cells12081208
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Roles of Arecoline and Arecoline N-Oxide in Oral Cancer and Strategies to Block Carcinogenesis

Abstract: Betel quid and areca nut are complex mixture carcinogens, but little is known about whether their derived single-agent arecoline or arecoline N-oxide (ANO) is carcinogenic, and the underlying mechanisms remain unclear. In this systematic review, we analyzed recent studies on the roles of arecoline and ANO in cancer and strategies to block carcinogenesis. In the oral cavity, flavin-containing monooxygenase 3 oxidizes arecoline to ANO, and both alkaloids conjugate with N-acetylcysteine to form mercapturic acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…In Taiwan, the primary cause of oral cancer is attributed to betel nut chewing, which has a significant association with the presence of arecoline. 28 Previous studies have indicated a substantial upregulation of β-catenin expression in the epithelium of oral cancer patients with a history of betel nut chewing, and arecoline has been shown to directly induce an increase in β-catenin protein expression. 29 Shiah et al.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, the primary cause of oral cancer is attributed to betel nut chewing, which has a significant association with the presence of arecoline. 28 Previous studies have indicated a substantial upregulation of β-catenin expression in the epithelium of oral cancer patients with a history of betel nut chewing, and arecoline has been shown to directly induce an increase in β-catenin protein expression. 29 Shiah et al.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the continuous deterioration of the social environment has affected people's physical health, people's lifestyle and dietary structure have been changed, and cancer patients have been increasing year by year 22,23 . Tumors are defined as vegetations that generate space‐occupying lumpy protrusions in patients due to sudden loss of normal regulation of cells in the body due to various carcinogenic factors 24–26 . Most patients with malignant tumors have bad living habits such as smoking, alcoholism, eating high energy and high fat, or malignant tumors in their tissues caused by exogenous factors such as external environmental stimuli, or malignant tumors in their local tissues caused by endogenous factors such as genetic factors, congenital or acquired immunodeficiency, and endocrine disorders 27 .…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Tumors are defined as vegetations that generate space‐occupying lumpy protrusions in patients due to sudden loss of normal regulation of cells in the body due to various carcinogenic factors. 24 , 25 , 26 Most patients with malignant tumors have bad living habits such as smoking, alcoholism, eating high energy and high fat, or malignant tumors in their tissues caused by exogenous factors such as external environmental stimuli, or malignant tumors in their local tissues caused by endogenous factors such as genetic factors, congenital or acquired immunodeficiency, and endocrine disorders. 27 The clinical manifestations of patients with malignant tumors are mainly divided into local and systemic manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous research has reported that several supplements, such as N -acetylcysteine or antioxidants like vitamins, manifest cancer risk reduction. For instance, N -acetylcysteine can conjugate with arecoline and produce mercapturic acid compounds, which are relatively less toxic and excreted through urine [ 196 ]. Thus, the combined use may be a promising strategy to reduce the potential toxicities and side effects of long-term arecoline use.…”
Section: The Potential Health Risks Of Areca Nutmentioning
confidence: 99%